Effect of the Cu capping thickness on the magnetic properties of thin Ni/Cu(001) films - Vaz, C; Lauhoff, G; Bland, J; Fulthorpe, B; Hase, T; Tanner, B; Langridge, S; Penfold, J (2001)
We have studied the effect of the Cu capping thickness (in the range 20 ≤ tcu ≤ 180 Å) on the magnetic and structural properties of ultrathin FCC 40Å Ni/Cu(001) films by means of magneto-optic Kerr effect (MOKE) magnetometry, polarised neutron reflection (PNR) and grazing incidence X-ray surface diffraction (GID) measurements. MOKE measurements show that perpendicular magnetic anisotropy (PMA) is observed for the whole of the Cu thickness range studied, while an increase of the coercive field with t Cu is found. The variation of the in-plane strain in the Ni film is shown to increase monotonously between 20 and 90Å Cu capping thickness from -1.60 ± 0.03% to -1.86 ± 0.07% as revealed by GID, while PNR measurements show a marked decrease in the Ni magnetic moment per atom with increasing Cu capping layer thickness, from 0.54 + 0.03 μB for tCu = 50Å to 0.45 ± 0.03 μ for tCu = 180Å. These results clearly show that a strain-induced reduction in the Ni magnetic moment per atom occurs. The increase in the coercive field is also attributed to the increase in the strain of the Ni film. © 2001 Published by Elsevier Science B.V.